The Scientist is Always True to Her Topic: For the Memory of Ekaterina K. Reva - Tatyana V. Strygina; Galina S. Zueva; Elena N. Serdobintseva; Natalya A. Shibleva; Darya V. Simchuk (Гуманитарный вектор)
The article is written in memory of Ekaterina Konstantinovna Reva, a Russian media researcher, Doctor of Philological Sciences, recently deceased in March, 2023. She was the head of the Journalism Department at Penza State University (2014–2023), the author of more than 100 articles, 2 monographs, 9 books for students. Her colleagues and students remember her professional biography. The key areas of her works concerned ethnojournalism in Russian magazines Nana, Dagestan, Narody Dagestana, Dosh, Druzhba Narodov. The doctoral thesis by E. K. Reva is a systematical research of the national printed media at the turn of the XIX century studying the forms and methods of reflecting the national culture of the peoples of North Caucasus. These research interests have become the basis for attracting a number of students and post-graduate students to scientific activity by E. K. Reva. She also constantly kept the contact to the community of media researchers from Russia, Kazakhstan, Belarus and Armenia. The authors of this article came to the conclusion about multifaceted and profound E. K. Reva’s contribution to the Russian science.